2019
DOI: 10.1002/cctc.201801760
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin: A New Biocatalyst for the Synthesis of 2‐substituted Benzoxazoles via Oxidative Cyclization

Abstract: Efficient and mild synthesis of a series of 2‐substituted benzoxazoles via oxidative cyclization catalyzed by hemoglobins reported here for the first time. Satisfactory yields (84 %–97 %) and mild reaction conditions make this method highly viable for practical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Hemoglobins, the most abundant hemoproteins in all groups of organisms, are ideal biocatalysts because of their low cost, commercial availability and good stability. Most studies to date have focused on using hemoglobins to catalyze traditional oxidation reactions and not have found widespread use in catalyzing new types of organic reactions . As part of our studies on the development of hemoprotein‐catalyzed organic reactions, we focused on the synthesis of indolizines catalyzed by hemoglobin via a multicomponent reaction (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Hemoglobins, the most abundant hemoproteins in all groups of organisms, are ideal biocatalysts because of their low cost, commercial availability and good stability. Most studies to date have focused on using hemoglobins to catalyze traditional oxidation reactions and not have found widespread use in catalyzing new types of organic reactions . As part of our studies on the development of hemoprotein‐catalyzed organic reactions, we focused on the synthesis of indolizines catalyzed by hemoglobin via a multicomponent reaction (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, enzyme catalytic promiscuity, the ability of a single active site of enzyme to catalyze new types of reactions that are different from natural ones, has been developed to widen the application of enzyme in organic synthesis. [22][23][24][25][26] In this area, lipases demonstrate the outstanding catalytic promiscuous abilities for their excellent stability and broad specificity, and many elegant works have been reported. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] As a further study to develop new types of organic reactions catalyzed by lipase, we reported here an efficient and mild method for the synthesis of N′-alkyl benzohydrazides (Scheme 1).…”
Section: S C H E M E 1 Synthesis Of N′-alkyl Benzohydrazides Catalyze...mentioning
confidence: 99%
“…Therefore, it remains necessary to develop a safer and mild reaction method for efficient synthesis of benzohydrazides. Recently, enzyme catalytic promiscuity, the ability of a single active site of enzyme to catalyze new types of reactions that are different from natural ones, has been developed to widen the application of enzyme in organic synthesis 22–26 . In this area, lipases demonstrate the outstanding catalytic promiscuous abilities for their excellent stability and broad specificity, and many elegant works have been reported 27–45 .…”
Section: Introductionmentioning
confidence: 99%
“…An interesting method to access the benzoxazole ring via oxidative cyclization catalyzed by hemoglobin was recently reported by Wang and co-workers. 46 The use of hemoglobin as a biocatalyst had been reported a few years earlier for the synthesis of (poly)aromatic hydrocarbons. 47 Following this work, hemoglobin from Vitreoscilla (VHb) was selected for its highest catalytic performance after screening different hemoproteins and enabled the synthe-sis of benzoxazoles 124 in excellent yields (up to 94%) from imine precursors 123.…”
Section: Short Review Synthesismentioning
confidence: 99%